Analysis of the psychiatric consultations for inpatients and from the emergency room in a university hospital: A comparison with studies from Turkey - YILDIZ, MESUT (KLINIK PSIKIYATRI DERGISI, 2018)
Objective: The aim of this research was to assess the characteristics of the consultations required in a psychiatric department of a university hospital, and the distribution of psychiatric disorders in hospitalized patients and patients admitted to the emergency room. Method: In the study, the data of 539 patients 18 years or older (48.67 +/- 20.91 years) (46.8% women) who were hospitalized and who presented to the emergency room between 01/01/2015 and 31/12/2015, and for whom a psychiatric consultation was requested were recorded onto a structured form. Patients' electronic databases were reviewed retrospectively for the specified date range. Descriptive statistical analyzes (frequency of data, distribution, mean, standard deviation) were performed for the data examined in the study. Results: Medical departments (42.9%), surgical departments (31.7%) and the emergency medicine department (25.4%) were the most frequently psychiatric consultation requesting departments. The most frequent requests for consultation were agitation (15.4%), depressive symptoms and signs (14.7%) and suicide attempts (12.2%). The most frequent psychiatric diagnoses were depressive disorders (19.5%), delirium (18.2%) and schizophrenia and other psychotic disorders (7.4%). Musculoskeletal diseases (17.4%), mental disorders (15.0%), oncologic diseases (14.1%) and suicide attempts (12.2%) were the primary diagnoses of patients. Discussion: Consultation and liaison psychiatry services have an important role in our relationship with other departments in medicine. Priority to training of depressive disorders, delirium and suicide attempts should be offered to healthcare providers working in these departments.
Keywords: Consultation; consultation liaison psychiatry; emergency room; general hospital; inpatient; LIAISON PSYCHIATRY; SERVICE